Some ADHD polymorphisms (in genes DAT1, DRD2, DRD3, DBH, 5-HTT) in case-control study of 100 subjects 6-10 age - Kopecková, Marta; Paclt, Ivo; Petrásek, Jan; Pacltová, Dagmar; Malíková, Marcela; Zagatová, Veronika (Neuro endocrinology letters, 2008)
BACKGROUND: Pharmacological approach is the most effective way of treatment of ADHD and its early application prevents from the progress of secondary disorders. The study on present neurotransmitter systems in pathology of ADHD can be helpful in selecting appropriate drug, since there are used various substances with different mechanisms of functioning in treatment of the hyperkinetic syndrome. METHOD: Within our study there were selected the genes of dopaminergic (DRD2, DRD3, DAT1), noradrenergic (DBH) and serotoninergic (5-HTT) systems. With the use of molecular-genetic methods based on association strategy "case-control" there were analysed genes including 11 polymorphisms. The presence of risk alleles was examined in comparison of the sample of 100 ADHD children to a control group of another 100 subjects, who were checked by child psychiatrists and examined with the Conners test in order to exclude eventual cases with ADHD symptoms. RESULTS: Our research suggests the association of some genes with ADHD. It could be concluded: 1) the risk of ADHD is significantly increased in the presence of one risk allele in genes DRD2 (O.R.=7,5), 5-HTT (O.R.=2,7) and DAT1 (O.R.=1,6). 2) The risk of ADHD is significantly increased at homozygotes for risk alleles in genes DRD2 (O.R.=54,8), 5-HTT (O.R.=6,7) and DAT1 (O.R.=6,6). For polymorphisms G444A and C1603T in DBH, which were detected by univariant analysis, haplotype analysis was performed and resulted in conclusion that: 3) the risk of ADHD is significantly increased in the presence of allele DBH +444A as well as in the presence of allele DBH +1603T (O.R.=15).
Keywords: Genetic Predisposition to Disease; Dopamine beta-Hydroxylase; jednonukleotidový polymorfismus; Male; DNA Mutational Analysis; Dopamine Plasma Membrane Transport Proteins; mužské pohlaví; membránové transportní proteiny pro serotonin; studie případů a kontrol; mutační analýza DNA; Serotonin Plasma Membrane Transport Proteins; dítě; Child; receptory dopaminu D2; Receptors, Dopamine D3; receptory dopaminu D3; ženské pohlaví; proteiny přenášející dopamin přes plazmatickou membránu; Humans; Receptors, Dopamine D2; frekvence genu; hyperkinetická porucha; rizikové faktory; Gene Frequency; Attention Deficit Disorder with Hyperactivity; genetická predispozice k nemoci; Female; Risk Factors; dopamin-beta-hydroxylasa; lidé; Case-Control Studies; Polymorphism, Single Nucleotide